Ageing in people with Prader–Willi syndrome: mortality in the UK population cohort and morbidity in an older sample of adults. Issue 3 (4th August 2014) - Whittington, J. E.; Holland, A. J.; Webb, T.
Abstract : Background: The past two decades have seen a great improvement in the care of people with Prader – Willi syndrome (PWS), particularly with regard to control of diet and behaviour management. Has this affected mortality rates or thrown up new issues regarding premature ageing or dementia? We investigated two aspects of ageing in people with PWS: (1) an estimate of mortality over 9 years in a cohort of people with PWS, originally recruited in 1998–2000; and (2) premature ageing or dementia in people aged ⩾40 years. Method: (1) A follow-up of the population-based 1998–2000 cohort to investigate the subsequent mortality rate; and (2) the recruitment and structured assessment of all members of the Prader–Willi Syndrome Association UK (PWSA-UK) aged ⩾40 years who agreed to participate. Results: Follow-up of the population-based 1998–2000 cohort gave a mortality rate of at least 7/62 over 9 years (1.25% per annum; 20 untraced), age at death was between 13 and 59 years. Twenty-six members of the PWSA-UK aged ⩾40 years were recruited, 18 of whom had a genetic diagnosis (gd) of PWS. Twenty-two (14 gd) showed no evidence of dementia. Four, with possible symptoms, are described in more detail; all are female, of maternal uniparental disomy (mUPD) genetic subtype, or have a disomic region, and all have a long history of psychotic illness. Conclusions: The mortality rate in people with PWS seems to be declining. The subgroup of people with PWS due to UPD or disomic region with female gender and a history of psychosis may be at risk of early onset dementia.